Efficient One-Pot Synthesis of 3,4-Dihydropyrimidin-2(1H)-ones via a Three-Component Biginelli Reaction - Giovanna Bosica (Molecules, 2021)
Multicomponent reactions are considered to be of increasing importance as time progresses due to the economic and environmental advantages such strategies entail. The three-component Biginelli reaction involves the combination of an aldehyde, a β-ketoester and urea to produce 3,4-dihydropyrimidin-2(1H)-ones, also known as DHPMs. The synthesis of these products is highly important due to their myriad of medicinal properties, amongst them acting as calcium channel blockers and antihypertensive and anti-inflammatory agents. In this study, silicotungstic acid supported on Ambelyst-15 was used as a heterogeneous catalyst for the Biginelli reaction under solventless conditions. Electron-poor aromatic aldehydes gave the best results. Sterically hindered β-ketoesters resulted in lower reaction yields. The reaction was carried out under heterogeneous catalysis to allow easy recovery of the product from the reaction mixture and recycling of the catalyst. The heterogeneity of the reaction was confirmed by carrying out a hot filtration test.